2012
DOI: 10.1186/1475-9276-11-37
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of predictors of teenage pregnancy and its prevention in a rural town in Western Nigeria

Abstract: IntroductionTeenagers younger than 15 are five times more likely to die during pregnancy or childbirth than women in their twenties and mortality rates for their infants are higher as well. This study was therefore designed to determine the recent prevalence and identify factors associated with teenage pregnancy in a rural town in Nigeria.MethodsThis study is an analytical comparative cross-sectional study. A total sample of all pregnant women attending the primary health care in Sagamu local government area, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
64
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 26 publications
15
64
4
2
Order By: Relevance
“…In sub Saharan Africa, anaemia, spontaneous abortion, prematurity and stillbirths are common symptoms of the disease. In Nigeria, the disease is a major public health challenge as malaria alone accounts for 11% maternal deaths annually (WHO, 2010;Amoran et al, 2012). However, no matter how alarming these statistics may sound some researchers still express doubts about their accuracy especially on the true status of malaria parasitemia in pregnancy in Nigeria (Eze et al, 2010).…”
Section: Malaria In Pregnancy: a Public Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…In sub Saharan Africa, anaemia, spontaneous abortion, prematurity and stillbirths are common symptoms of the disease. In Nigeria, the disease is a major public health challenge as malaria alone accounts for 11% maternal deaths annually (WHO, 2010;Amoran et al, 2012). However, no matter how alarming these statistics may sound some researchers still express doubts about their accuracy especially on the true status of malaria parasitemia in pregnancy in Nigeria (Eze et al, 2010).…”
Section: Malaria In Pregnancy: a Public Healthmentioning
confidence: 99%
“…In endemic countries like Nigeria, 20% of malaria parasitemia in pregnancy are asymptomatic, with susceptibility to parasitemia common in primgravidae (Desai et al, 2007;, Amoran, 2012. Agomo et al (2009), stated that amongst the factors identified to increase the risk of malaria infection include; young maternal age (<20years), and gravidity (primigravidae).…”
Section: Nzeako Et Al Prevalence Of Malaria In Pregnant Women Attendmentioning
confidence: 99%
See 2 more Smart Citations
“…It may also add to the progression of poverty and its added problems. 5,6 Teenage pregnancies are frequently 3,7,8 The problem of adolescent pregnancy needs to be addressed with a multidimensional attitude. The burden of adolescent pregnancy problems can be reduced by widespread education about contraception which also involves provision of readily available, safe and appropriate contraceptive methods.…”
Section: Introductionmentioning
confidence: 99%